The Lego Halloween games book - Kosara, Tori, 1985-; March, Julia (DK Publishing, 2024)
Accompanied by Halloween-themed LEGO elements, including a skeleton minifigure, this frightfully fun activity book is filled with ghastly games, eerie escape room puzzles, monster mashups and more.